Digitalisasi Sebagai Formulasi Transisi Menuju Transparasi Perpajakan - Yunus Darmono; Amir Junaidi; Ismiyanto Ismiyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research answers the problem formulation of the urgency of tax digitalization as a transition formulation towards tax transparency and determines the various obstacles in implementing tax digitalization as a transition formulation towards tax transparency. Transparency is one component of good governance, including in the field of taxation. In order to realize aspects of transparency, the government issued a tax digitalization policy. The hope is that digitalization of taxation can improve the weaknesses of conventional taxation and be able to formulate a transition or change towards transparent taxation. This sociolegal research uses a qualitative and descriptive approach with the main aim of searching for data on the implementation of tax digitalization as well as at the regional level within the scope of its implementation by employees of the Primary and Middle Tax Offices in the City of Surakarta. The results of the research are the urgency of digitizing taxation as a transition formulation towards tax transparency as a response to electronic and e-Government based government systems as well as increasing ease of tax access. Meanwhile, various obstacles in implementing tax digitalization as a formulation of the transition towards tax transparency include the transition from conventional taxation to digital taxation as well as budget problems and system maintenance.